Bruxismo noturno, bullying verbal escolar e satisfação de vida em adolescentes brasileiros - Livia Bonfim Fulgencio (2016)
The aim of this study was to investigate the association between probable sleep bruxism, school verbal bullying, economic class and life satisfaction in adolescents. This study will be presented in two papers format: the first cross-sectional population-based and the second, a case-control study nested in the cross-sectional study. The cross-sectional population-based study was conducted with a sample of 1344 adolescents aged 13 to 15 years of age, enrolled in schools in Itabira, Brazil. Data on the likely sleep bruxism and economic status were obtained through a questionnaire answered by parents. In turn, the information about the involvement in episodes of verbal bullying and school life satisfaction were collected through questionnaires answered by adolescents. The sleep bruxism has been identified as the minimum criteria of the International Classification of Sleep Disorders (ICSD), while questions about the school verbal bullying were based on the questionnaire from the National School of Health (PeNSE). To qualify economically families, they were adopted the criteria formulated by the Brazilian Association of Research Companies (ABEP). The life satisfaction was assessed using the Multidimensional Scale for Adolescents Life Satisfaction (EMSVA). Data were analyzed using bivariate tests and Poisson regression with robust variance. According to parents' reports, 205 (15.3%) adolescents were likely nocturnal bruxism. In relation to the school verbal bullying, 10.9% of adolescents were victims, 17.2% were aggressors and 5.9% were both victims and perpetrators. The higher prevalence of sleep bruxism was observed among adolescent victims of school verbal bullying (OR: 6.31; 95% CI: 4.78 to 8.32) and victims/perpetrators (PR: 5.27; 95% CI: 3.82 -7.27). The sleep bruxism was associated also with high economic class (PR: 1.51; 95% CI: 1.23-1,86) to higher life satisfaction scores in self domains (RP: 1.04; 95% CI: 1, 00 to 1.08), school (PR: 1.05; 95% CI: 1.02 to 1.09) and self-efficacy (OR: 1.07; 95% CI: 1.03 to 1.12) and low scores satisfaction in the non-violence (PR: 0.96; 95% CI: 0.93-0.99). In the case-control study, adolescents who participated in the cross-sectional study were divided into two groups according to the presence/absence of probable sleep bruxism. The case group was composed of 103 adolescents with sleep bruxism and the control group had 206 participants without sleep bruxism. The groups were matched according to gender and age of adolescents and we adopted a ratio of two controls for each case. The association between the dependent variable (sleep bruxism) and independent variables (economic class and school verbal bullying) was verified by conditional logistic regression models unadjusted and adjusted. In the analysis of this data, it was found that adolescents with sleep bruxism had a six times greater chance of having been exposed to episodes of school verbal bullying (OR: 6.08; 95% CI: 4.25 to 8.72) compared to adolescents in the control group. Given these results, it was concluded that sleep bruxism was significantly associated to school verbal bullying in both studies. In contrast, the association between sleep bruxism and economy class was only observed in cross-sectional study.